Development of Islamic websites evaluation guidelines - Aliyu, Mansur; Mahmud, Murni; Md Tap, Abu Osman; Hussein, Idyawati (Taylor and Francis - Balkema, 2014)
This study explored user perceptions of the Islamic Website Evaluation Guidelines (IWEG). It identified ten latent factors from exploratory factor analysis using orthogonal rotation method. The ten latent factors of the IWEG extracted indicated satisfactory reliability scores. A survey of 450 university students was conducted. All the respondents self-reported to have had experience using Islamic websites. The 84 features that were explored were classified under the ten latent factors extracted. Each of the 84 extracted items loaded cleanly on its factor between the range of .411 and .841 with no cross-loadings on other factors. Overall, three dimensions were formulated to better represent the ten latent factors: Content (objectivity, reliability, credibility, format), Islamic (identity, services, ethical values, symbols), and Impact (website use, positive impact). The overall analyses of the results were discussed. The practical implications of the findings were highlighted.